(untitled) (Research, Society and Development, 2021)
This research aims to discuss and analyze the forms of integrated management of a hydraulic basin in Sumé, making a survey of recent information in order to keep water resources in balance. To this end, we used the methodological resource of bibliographic survey and application of integrated management subdivided into a master plan for water resources, information systems, water bodies framework, granted and collections. As aresult, it is noteworthy that the water did not comply with the consumption potability standards established by Ordinance 2914/11 of the MS and Resolution 357/05 of CONAMA, according to a study carried out with a sample of water from the basin, in addition according to a survey conducted with consumers of water from the Sumé basin, according to them the water shows noticeable changes in its composition according to the smell and turbidity of the water offered by the supply system and the Paraíba-CAGEPA Water and Sewage Company. In view of the results achieved throughout the research, it is concluded that it is possible, within the existing environmental framework, to change the form of appropriation and use of environmental resources, while providing this resource to human beings with the necessary quality for consumption without finding irregularities in supply according to water quality.